2014
DOI: 10.3928/01477447-20140728-92
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Neuropathy as a Result of Anconeus Epitrochlearis

Abstract: After carpal tunnel syndrome, cubital tunnel syndrome is the second most common compression neuropathy in the upper extremity. Various sites of ulnar nerve compression at the elbow exist, with the most common being between the 2 heads of the flexor carpi ulnaris. Other potential sites include the arcade of Struthers, the space between Osborne's ligament and the medial ulnar collateral ligament, the medial epicondyle, the medial head of the triceps, and the medial intermuscular septum. The anconeus epitrochlear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…2,11 Anconeus epitrochlearis-associated ulnar neuropathy, however, usually has different characteristics than idiopathic cubital tunnel syndrome, including onset at a younger age and more rapid progress. 3,8,12 A group of patients who had anconeus epitrochlearis-associated ulnar neuropathy had a shorter duration of symptoms. 12 Some authors noted that medial elbow pain is more pronounced than sensory symptoms in these patients, and that was the case in the current patient.…”
Section: A B E989mentioning
confidence: 99%
See 2 more Smart Citations
“…2,11 Anconeus epitrochlearis-associated ulnar neuropathy, however, usually has different characteristics than idiopathic cubital tunnel syndrome, including onset at a younger age and more rapid progress. 3,8,12 A group of patients who had anconeus epitrochlearis-associated ulnar neuropathy had a shorter duration of symptoms. 12 Some authors noted that medial elbow pain is more pronounced than sensory symptoms in these patients, and that was the case in the current patient.…”
Section: A B E989mentioning
confidence: 99%
“…2 However, the clinical diagnosis of ulnar neuropathy at the elbow as a result of this muscle variation is rare, with an unknown prevalence. 3 The anconeus epitrochlearis muscle is a congenital accessory muscle between the medial humeral epicondyle and the olecranon that covers the posterior aspect of the cubital tunnel. It is probably an atavistic structure.…”
Section: A B E989mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were either about anatomical findings in cadavers or those found incidentally in the operating field [2][3][4][5][6][7][8][9][10][11]. Although the majority of anomalous muscles are asymptomatic, they may occasionally produce persistent pain, unexplained mass, or compression neuropathy necessitating surgical excision [7,8,[11][12][13][14][15][16][17]. Despite several anatomical descriptions, the actual reports of the clinical application of such anomalous muscles are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There are also rare reports of unusual findings including ulnar nerve compression secondary to anatomic variations in the triceps musculature. [5][6][7][8][9][10] We present a case of ulnar nerve compression neuropathy at the elbow secondary to an abnormal snapping medial head of the triceps.…”
Section: Introductionmentioning
confidence: 99%